Let-7 microRNAs and Opioid Tolerance - HE, YING; WANG, ZAIJIE JIM (Frontiers in Genetics, 2012)
This chapter will focus on the role of microRNAs (miRs) in regulating the actions of opioid drugs through the opioid receptors. Opioids, such as morphine, are analgesics that are used for treating many forms of acute and chronic pain. However, their chronic use is limited by undesirable effects such as opioid tolerance. The µ opioid receptor (MOR) is the primary receptor responsible for opioids’ analgesia and antinociceptive tolerance. The long 3’-untranslated region (3’-UTR) of MOR mRNA is of great interest since this region may contain elements for the post-transcriptional regulation of receptor expression, such as altering the stability of mRNA, influencing translational efficiency and controlling mRNA transport. Indeed, it was reported that human MOR expression was increased after a 712 bp sequence, immediately downstream of the stop codon, was removed. MicroRNAs are small noncoding RNA molecules that exert their functions through base-pairing with partially complementary sequences in the 3’-UTR of target mRNAs, resulting in decreased polypeptide formation from those mRNAs. Since the discovery of the first miR, lin-4 in C. elegans, hundreds of miRs have been identified from humans to viruses, which have provided a crucial and pervasive layer of post-transcriptional gene regulation. The nervous system is a rich source of miR expression, with a diversity of miR functions in fundamental neurobiological processes including neuronal development, plasticity, metabolism and apoptosis. Recently, the let-7 family of miRs is found to be a critical regulator of MOR function in opioid tolerance. Let-7 is the first identified human miR. Its family members are highly conserved across species in sequence and function. In the review, we will present a brief review of the opioid receptors, their regulation, and opioid tolerance as well as an overview of miRs and a perspective how miRs may interact with MOR and serve as a regulator of opioid tolerance.